Re-Interpreting “God of Perception”: Understanding Cosmopolitan Sufism of Ibn Arabi - Yaqin, Ainul; Shobah, Muhammad Nurush (Proceedings of International Conference on Muslim Society and Thought, 2024)
This article analyses the concept of “God of Perception” according to Ibn `Arabi’s perspective as an image of cosmopolitanism in his thought. This contribution of his thought implies the construction of awareness of the inevitability of religious plurality. The type of this research is library research, then the collected data is analyzed with a hermeneutic approach to Schleiermacher reconstruction. After conducting an analysis, the researcher gets the conclusion that: first, Ibn `Arabi through his key concept of “tajalli” thinks about the idea of “God of Perception”, in which he has criticized the existence of truth claims to the beliefs each individual. Second, Ibn ’Arabi through his “The Religion of Love” seeks to lead every human being to different religions towards harmony and tolerance based on love and peace. Third, Ibn `Arabi’s cosmopolitanism here same as his “Religion of Love”, which in turn pushes tolerance to a more realistic level.